PEMIDANAAN PELAKU TINDAK PIDANA KEKERASAN FISIK TERHADAP AYAH TIRI (PUTUSAN NO. 345/PID.SUS/2021/PN BGL): Punishment Of Perpetrators Of Physical Violence Against Stepfather (Decision Number 345/Pid.Sus/2021/Pn Bgl) - Muhammad Ar Rahman Wibowo; Azmi Syahputra (Faculty of Law, Universitas Trisakti, 2024)
This research discusses a case between Deni Saputra who was the perpetrator of a crime of domestic violence against his stepfather in decision no. 345/Pid.Sus/PN Bgl. There are two formulations of the problem raised, namely whether the perpetrator of the criminal act meets the elements of the offense of Article 44 paragraph (2) of the Domestic Violence Law and whether the punishment for the perpetrator who caused serious injury is appropriate or not, a prison sentence of 3 years and 6 months is imposed. The research method is descriptive analytical with secondary data analyzed qualitatively, type of research is normative juridical. The results of the research and discussion show that the actions of the perpetrator of the crime of physical violence against the stepfather were considered appropriate in accordance with Article 44 paragraph (2) of the Domestic Violence Law as the punishment was considered too light. The conclusion in this research is that the judge in deciding on a sentence of 3 years and 6 months was not in accordance with article 44 paragraph (2) of the Domestic Violence Law, namely 10 years in prison for the purpose of criminalizing the perpetrator in order to provide a deterrent effect for his actions.